Analisis Dampak 5 (Lima) Provinsi Destinasi Pariwisata Super Prioritas Indonesia Terhadap Produk Domestik Regional Bruto - Manalu, Herna Uli; Rahmadana, Fitri; Arwansyah, Arwansyah (Journal of Business and Economics Research (JBE), 2025)
The purpose of this study is to examine the impact of tourism on Gross Regional Domestic Product (GRDP) in five provinces in Indonesia identified as super-priority destinations: North Sumatra, Central Java, West Nusa Tenggara, East Nusa Tenggara, and North Sulawesi. This study includes three independent variables: number of tourists, number of tourist attractions, and room occupancy rate, which are analyzed partially and simultaneously. This research uses quantitative methods, with secondary data from the Central Bureau of Statistics (BPS) covering the period 2018 to 2023. The analytical approach used was panel data regression with Eviews 12 software, and the Common Effect Model (CEM) was selected based on the results of the Chow, Hausman, and Lagrange multiplier tests. The findings of this study reveal that the three variables have a favorable and substantial impact on tourism sector GRDP. The three factors can collectively explain 65.04% of the variation in GRDP. The findings highlight the importance of increasing the number of tourists, improving tourist attractions, and optimizing accommodation occupancy rates in driving regional economic growth. Consequently, the findings of this study are intended to help local governments develop successful and long-term tourism programs.